Characterization of the Ferroptosis-Related Genes for Prognosis and Immune Infiltration in Low-Grade Glioma - Yan, Xiuwei; Ji, Hang; Liu, Zhihui; Ma, Shuai; Dong, Jiawei; Jiang, Xiaoyan; Hu, Xueyan; Wang, Fang; Zhao, Hongtao; Jin, Jiaqi; Zhang, Jiheng; Wang, Nan; et al. (Frontiers in Genetics, 2022)
Background: Although ferroptosis has been validated to play a crucial role in some types of tumors, the influence of FRGs on the immune microenvironment in low-grade glioma (LGG) remains unclear. In this research, we screen the ferroptosis-related genes (FRGs) to assess the prognosis value and immune microenvironment in LGG, to provide reliable diagnosis and treatment evidence for the clinic. Methods: A total of 1239 patients of LGG were selected for subsequent analyses from The Cancer Genome Atlas, Chinese Glioma Genome Atlas, and the Repository of Molecular Brain Neoplasia Data datasets. Univariate Cox regression analysis was used to screen for prognostic FRGs. Consensus clustering was utilized to determine ferroptosis subtypes of LGG patients. Next, The prognostic model was constructed based on differentially expressed FRGs and validation in the validating datasets. The immune microenvironment, biological pathway, and hypoxia score were explored by single-sample gene set enrichment analysis. The potential response of chemotherapy and Immune checkpoint blockade therapy was also estimated. In addition, the correlation between the risk score and autophagy-related genes was examined by the Pearson correlation coefficient. Results: Three ferroptosis subtypes were identified by consensus clustering for prognostic FRGs which exhibited different outcomes, clinicopathological characteristics, and immune microenvironment. Afterward, a prognostic model that performed great predictive ability based on nine prognostic FRGs have been constructed and validated. Moreover, The prognostic model had the potential to screen the sensitivity to chemotherapy and immunotherapy in LGG patients. Finally, we also found that the prognostic model has a great connection to autophagy and hypoxia. Conclusions: We developed a ferroptosis-related prognostic model which strongly linked to the diagnosis, treatment, prognosis, and recurrence of LGG, and reveals the connection between ferroptosis and tumor immune microenvironment.